Fitspiration Model: The influence of body image on self-compassion is mediated by the intensity of social media use. - Tanti Saputri; Awaludin Ahya; Moersito Wimbo Wibowo (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study investigates the link between self-compassion and body image, as mediated by the intensity of social media use. According to earlier studies, women's body satisfaction may suffer when they are exposed to idealized body pictures on social media. Self-compassion, however, could serve as a buffer against these impacts. This study uses a correlational design and an online survey to get data from young adult women between 18 and 25. The Body Appreciation Scale (BAS) measures body image, the Self-Compassion Scale (SCS) measures self-compassion, and a questionnaire gauges the degree of social media use. According to the results of the path analysis, self-compassion does not moderate the link between body image and the intensity of social media use. These results imply that although social media involvement is influenced by body image, self-compassion may not be sufficient to lessen its effects. This study emphasizes the need for more investigation into other mediating variables and therapies that support a healthy body image in the digital age.